PENGARUH PENGGUNAAN APLIKASI NETFLIX TERHADAP PERILAKU ADDICT REMAJA - Muhammad Iqbal Febian Rizki (2023)
This study aims to determine the effect of the use of the Netflix application on the behavior of adolescent addicts, which is currently an activity of watching streaming carried out by the community, especially teenagers with regional boundaries in DKI Jakarta. The type of research used in this study is explanatory research which aims to see the relationship between variables or look for causation of the variables to be studied. The use of the Netflix application as the independent variable (cause) and Teen Addict as the dependent variable (effect).